Le prédateur inconnu : engagement et distanciation dans les prédations marines - Estienne Rodary (VertigO)
The connections between humans and non-human animals have become a teeming field of research and media focus in recent years, in which the place of predators occupies a special position (Rodary, 2019). Because they are threatened and menacing, predators crystallize the politics of nature at its most demanding for good life on Earth. The first victims of Neolithic and modern dynamics of ecumene expansion, they now seem to be regaining a legitimate place in the wild part of the world that ecology is calling for (Maris, 2018). However, policies are struggling to define this part of the world, torn as they are between the logics of distancing/contiguity and commitment/security. This is all the more true given that the ways in which human and non-human predators coexist maintain a complex relationship with knowledge, in which the production of ignorance is a determining factor. Ocean spaces, long considered as the last wild part of the world due to their both material and cognitive characteristics, are now crossed by a logic of frontier (Fache et al., 2021) incorporating marine predators in the toils of these issues of engagement and distancing. However, this crossing into marine environments also brings about transformations, linked to the environmental and existential conditions specific to the oceans. The fact that these spaces are uninhabitable for humans means that those who venture into them are particularly ignorant and vulnerable. The knowledge and use of these spaces is thus mediated by technical artifacts (fishing lines, sonic and visual waves) that do not fundamentally reduce trans-specific otherness. From then on, oceanic "diving" (on the surface or at depth) generates an intraspecific construction of mutual aid (Gilroy, 2018) but exacerbates the interspecific fragility of humans in the face of predators. In this context, the article intends to questions the historicization of the animal and the construction of the individual predator as an actor beyond a species determinant. But contrary to the currently dominant discourse on the happy happy and apolitical trans-specific connection, it politicizes the encounter between humans and marines species and explores ways of restraining anthropic expansion based on recognition of the distance to be maintained between the human predator and marine predators.